Key factors for increased tip-apex distance when treating intertrochanteric fractures with InterTAN nails - Zhu, Naifeng; Wu, Lianxia; Han, Xiaofeng; Qian, Zhonglai (Frontiers in Bioengineering and Biotechnology, 2024)
Background The tip-apex distance is a key factor in predicting implant cut-out after intramedullary fixation for intertrochanteric fractures. This study aimed to evaluate the factors associated with an increased tip-apex distance when treating intertrochanteric fractures using an InterTAN nail. Methods and Material We retrospectively analyzed patients with intertrochanteric fractures who underwent InterTAN nail insertion between January 2017 and March 2022 at our hospital. Medical and radiological data were collected. Measurements of preoperative factors and postoperative factors were performed accordingly. Multivariate logistic regression analysis was performed to determine the statistically significant variables of the tip-apex distance. Results This study included 102 patients with intertrochanteric fractures. The average tip-apex distance measured 22.4 ± 7.1 mm, ranging from 9.3 to 48.0 mm. The length of the femoral neck on the non-fractured side, lag screw placement in the sagittal plane (center-inferior, superior) and coronal plane (posterior), and the angle between the line of the proximal nail axis and the femoral long axis were identified to be statistically significant factors for the tip-apex distance. Conclusion To obtain a shorter tip-apex distance, we recommend a medial trochanteric entry point to minimize the angle between the line of the proximal nail axis and the femoral long axis. Additionally, sufficiently deep central insertion of the lag screw was advised in both the sagittal and coronal planes.